2020
DOI: 10.1007/s11051-020-04840-8
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle number concentration measurements by multi-angle dynamic light scattering

Abstract: We present the use of Multi-angle Dynamic Light Scattering (MADLS®) for the measurement of nanoparticle concentration. We describe the theory of the method and its application to nanoparticles made of gold, silica and polystyrene, with diameters ranging from 30 to 400 nm, and demonstrate some of the limitations with particles of sizes 500 nm and above. We evaluate the method accuracy, linearity and reproducibility, as well as the operational nanoparticle concentration and size range. We show that the concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 37 publications
3
47
0
Order By: Relevance
“…To investigate the change of particle size with the addition of L-PaF to ME further, we performed MADLS measurements (Figure 1) (Naiim et al, 2015;Austin et al, 2020). These results confirmed that L-PaF is heterogeneous with four distinct particle size populations based on intensity-based measurements, however particle numbers indicated that the smallest species (∼8 nm) was dominant.…”
Section: L-paf Interacts With Mementioning
confidence: 62%
“…To investigate the change of particle size with the addition of L-PaF to ME further, we performed MADLS measurements (Figure 1) (Naiim et al, 2015;Austin et al, 2020). These results confirmed that L-PaF is heterogeneous with four distinct particle size populations based on intensity-based measurements, however particle numbers indicated that the smallest species (∼8 nm) was dominant.…”
Section: L-paf Interacts With Mementioning
confidence: 62%
“…Thanks to a number of international efforts in recent years, this situation is improving. [2][3][4][5][6][7][8][9][10][11][12] Documentary standards have been developed within the International Organization for Standardisation (ISO) for a number of techniques capable of performing number concentration measurements including population-averaging methods such as: small angle X-ray scattering (SAXS), 13 dynamic light scattering 14,15 and centrifugal liquid sedimentation (CLS), 16,17 as well as particle-counting methods such as, single particle inductively coupled plasma mass spectrometry (spICP-MS), 18 particle tracking analysis (PTA), 19 differential mobility analysis with integrated condensation particle counter 20 and resistive pulse sensing (RPS). 21 Many of these standards, however, describe aspects of particle size analysis rather than measurement of number concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Multiangle dynamic light scattering (MADLS) allows for a higher-resolution size determination of multimodal samples, by using three different detection angles (back, side, and forward) and combining the information obtained into one angle-independent particle size distribution. An extension of MADLS is particle concentration measurements giving the total particle concentration and the particle concentration for each mode present in a sample [ 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%